Teacher Learning Strategies In Shaping Student Character In Islamic Cultural History Lessons At SMP 45 Latukan Karanggeneng Lamongan - Syaipudin, Latif (Jurnal Pendidikan Indonesia, 2023)
Teachers are required to improve the quality of learning and present learning that is fun for students. One way that a teacher can do this is by mastering learning strategies. Through SKI subjects, it is expected to be able to instill the character of students who have better manners, manners and life values. The problem formulations in this study are: 1) How is the planning of SKI teacher learning strategies in shaping the character of students at SMP 45 Latukan Karanggeneng?, 2) How is the implementation of the SKI teacher's learning strategy in shaping the character of students at SMP 45 Latukan Karanggeneng?, 3) How is the evaluation of the SKI teacher's learning strategy in shaping the character of students at SMP 45 Latukan Karanggeneng? The research approach uses qualitative, with descriptive research type. Data collection techniques using observation, interviews and documentation. The results of this study show: 1) Planning the learning strategy of SKI teachers in shaping the character of students at SMP 45 Latukan Karanggeneng is carried out to instill human values that have morals, character, morals, character, and behavior of a person that is reflected in goodness through the preparation of learning tools so that difficulties can be overcome such as making lesson plans, media, strategies and other learning resources so that SKI learning remains fun. 2) Implementation of SKI teacher learning strategies in shaping the character of students at SMP 45 Latukan Karanggeneng is done through delivery on SKI learning materials. Implementation of learning will be successful if it has the support of both students and teachers. As a party who has the responsibility as a facilitator, the teacher must be able to make learning interesting. 3) Evaluation of the SKI teacher's learning strategy in shaping the character of students at SMP 45 Latukan Karanggeneng still requires improvement because there are still many teachers who have not been able to use technology as a learning aid, so using the lecture method will make students bored. So that the cultivation of character has not been fully conveyed.